(Re)politicising 'the governmental': Resisting the Industrial Relations Act 1971. (August 2019) - Warner, Sam
This article is an account of the failure of the Industrial Relations Act that places resistance at its heart. This is achieved through application of the (de/re)politicisation framework, uncovering how this attempt to depoliticise the reform of industrial relations was resisted and re-politicisation achieved. The article argues that (re)politicisation is best understood through an analysis of informal processes of struggle involving non-governmental actors. By adopting a critical political economy perspective informed by Open Marxism, the so-called state-centrism of the governmental level is eschewed. New archival evidence demonstrates the importance of not only addressing the imposition of this governing strategy, but also the active role of organised labour when engaged in resistance to it. Thus, this article steps 'beyond the governmental' to argue that adequate conceptualisation of resistance at the societal level is a necessary part of understanding how depoliticised governing is shaped, imposed, transformed and potentially undermined.